The systematic use of analogies in teaching abstract concepts in chemistry: Effects on achievement and retention - Rebollos, David S. (Animo Repository, 1997)
This study investigates the effect of systematic use of analogies in teaching selected abstract topics in chemistry.The study made use of the nonequivalent control group design. The achievement and subject matter retention of students taught with the use of pictorial-verbal and verbal analogies based on Glynn's et al (1989) Teaching-with-Analogy (TWA) model was compared with a control group. Significant differences in achievement and subject matter retention between students with different analogical reasoning ability level and between genders and interaction effects among teaching approach, analogical reasoning ability level and gender were also determined. Attitudes and views of students concerning the use of analogies in teaching and learning chemistry concepts were also solicited through interviews from randomly selected students who were taught abstract chemistry concepts using analogies. The sample consisted of 81 first year Bachelor of Arts (nonscience majors) with average age of 17 years and enrolled in two Chemistry 101 (General & Inorganic Chemistry) classes at the Western Mindanao State University, Zamboanga City.Main research instruments used were the Analogical Reasoning Ability Test and the 50-item Chemistry Achievement Test (CAT). Students scores in the posttest and delayed posttest were analyzed using ANCOVA. Analysis of the F-test results at the .05 level of significance showed the following: 1) There was a significant difference in achievement between students in the experimental group and those in the control group. Students who received analogical instruction scored higher in the posttest. 2) There was a significant difference in achievement between students with high analogical reasoning ability level and students with low analogical reasoning ability level for both experimental and control groups. 3) There was no significant difference in achievement between male students and female students for both experimental and control groups. 4) There were no interaction effects between and among teaching approach, analogical reasoning ability level and gender on achievement. 5) There was no significant difference in subject matter retention between students. 6) There was a significant difference in subject matter retention between students with high analogical reasoning ability level and students with low analogical reasoning ability. 7) There was no significant difference in subject matter retention between male students and female students for both experimental and control groups. 8) There were no interaction effects between and among teaching approach, analogical reasoning ability level and gender on subject matter retention.The study concluded that the use of pictorial-verbal and verbal analogies based on the TWA model is a useful strategy for improving achievement in abstract topics in chemistry. It can also be concluded that both achievement and subject matter retention in abstract topics in chemistry are dependent on the analogical reasoning ability levels of students.